Pengaruh Kepemilikan Institusional, Kepemilikan Asing, Dan Leverage Terhadap Pengungkapan Corporate Social Responsibility Pada Perusahaan Sektor Energi Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2022 - Rohman, Taufiqur (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to examine The Effect of Institutional Ownership, Foreign Ownership, and Leverage on Corporate Social Responsibility Disclosure simultaneously and partially in Energy Sector Companies Listed on the Indonesia Stock Exchange for the 2017-2022 Period. The type of research that used in this research is quantitative research with associative descriptive method. This study uses secondary data obtained from annual reports of energy sector companies for the period 2017 – 2022 which are listed on the Indonesia Stock Exchange. And the technique is used a purposive sampling technique that is in accordance with the criteria as a determination of the research sample. Data analysis was performed using multiple regression analysis with the Statistical Package for the Social Sciences (SPSS) 2.5 program tool. The results of the analysis conclude that institutional ownership, foreign ownership and leverage simultaneously have an influence on CSR disclosure. Institutional ownership partially has a significant positive effect on Corporate Social Responsibility Disclosure. Foreign ownership partially has a significant negative effect on Corporate Social Responsibility Disclosure. Leverage partially has a positive but not significant effect on Corporate Social Responsibility Disclosure.